(untitled) (Oxford, 1998)
The book includes: classroom techniques covering the four skills of speaking, listening, reading and writing; aids; testing; problem classes; phonetics; and syllabus design. All the topics contain practice material such as axercises, activities, and discussion points, as well as references to existing textbooks. There is also a glossary, and index, and a bibliography for further reading
Keywords: english language - study and teaching